Spiritual attachment in Islam and Christianity: similarities and differences - Miner, Maureen; Ghobary, Bagher; Dowson, Martin; Proctor, Marie-Therese (2014)
Theory and measurement of attachment to God have largely been developed from a western Christian perspective. However, the relevance of the attachment construct for Muslims should be examined if it is to contribute to a greater understanding of Islamic spirituality and psychological health. In this paper, we explore similarities and differences between Islamic and Christian understandings of human-divine relationships. We consider evidence of a common core of attachment themes of relevance to both religions, and whether different dimensions are emphasised in religious writings of the two traditions. This theoretical work is foundational for cross-cultural/cross-religious research. We argue that a core difference between the two faiths is that Muslims approach God in a less direct, more mediated fashion than Christians. Such differences have important implications for the wording of self-report assessment items and approaches to interventions designed to increase the security of Christians' and Muslims' attachment to God and mental health.
Keywords: Christianity; Islam; attachment to God; Comparative Religion; psychological practice